Association between Insulin Resistance and Cardiovascular Risk Factors in Polycystic Ovary Syndrome Patients - Miriam da Silva Wanderley; Lara Cristina Ribeiro Pereira; Carla Borges Santos; Vinícius Santos da Cunha; Mariam Viviane Jovino Neves (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To analyze the association between the indirect methods of evaluating insulin resistance (IR) and blood pressure, anthropometric and biochemical parameters in a population of polycystic ovary syndrome (PCOS) patients. Methods Cross-sectional study performed at the Hospital Universitário de Brasília (HUB, in the Portuguese acronym) involving PCOS patients diagnosed from January 2011 to January 2013. Four indirect methods, namely, fasting blood insulin level, fasting glucose/insulin ratio (G/I), homeostatic model-assessment-insulin resistance (HOMA-IR), and the quantitative insulin sensitivity check index (QUICKI), were used to obtain the IR diagnosis. The data were analyzed using the test of proportions, the Chisquare test, and Fisher exact test, when indicated. Results Out of the 83 patients assessed, aged 28.79 ± 5.85, IR was found in 51.81- 66.2% of them using the G/I ratio and the QUICKI, respectively. The test of proportions did not show a significant difference between the methods analyzed. The proportion of IR diagnoses was statistically higher in obese women than in women with normal body mass index (BMI). We observed a statistically significant association between all the methods for diagnosing IR and BMI, waist circumference (WC) and lipid accumulation product (LAP). With regards to arterial hypertension (AH), we observed a significant association according to three methods, with the exception of the ratio G/I. Conclusion Insulin resistance prevalence varied according to the diagnostic method employed,with no statistical difference between them. The proportion of IR diagnoses was statistically higher in obese women than in women with normal BMI.We observed a significant association between IR andWC, BMI, LAP, as well as dyslipidemia and AH in a high proportion of patients.